(untitled) (INSTITUTIO : Jurnal Pendidikan Agama Kristen, 2022)
The purpose of this paper is to disscuss the issue of the urgency of implementing Christian Education in early childhood learning. The purpose of this research is to answer why Christian education is considered important to be implemented in early childhood learning. Qualitative with descriptive is the method used in this research, carried out in PAUD/TK Dharma Wanita Kalasey I. Informants are headmaster, teachers, and parents. Data obtained through interviews, observations, and documentation then analyzed using data reduction, data display, and drawing conclusions. The result of this study found that the creativity and innovation of Christian education greatly influenced the implementation of Christian education to life. General educationcan be inspired by material of christian education when good and intelligent integration is established. Life of christian education on early childhood will be experienced in the efforts of attention and collaboration from the school, government, church and parents after the understand, appreciate, and realize correctly about the essence and the importance christian education for early childhood.